EJ12 girl hero: jump start - MCFARLANE, SUSANNAH; SUSANNAH MCFARLANE (New York Scholastic, 2010)
10-year-old spy Emma Jacks (EJ12) must conquer her fear of high jumps in a gymnastics competition while simultaneously stopping the evil agency SHADOW from destroying a rainforest habitat.
Keywords: who acts as a secret agent for the organization SHINE; with confidence, determination, and bravery, one can overcome personal fears and self-doubt, both in "secret" life and everyday challenges